2022
DOI: 10.1186/s12974-022-02603-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Schwann cell pannexin 1 attenuates neuropathic pain through the suppression of inflammatory responses

Abstract: Background Neuropathic pain is still a challenge for clinical treatment as a result of the comprehensive pathogenesis. Although emerging evidence demonstrates the pivotal role of glial cells in regulating neuropathic pain, the role of Schwann cells and their underlying mechanisms still need to be uncovered. Pannexin 1 (Panx 1), an important membrane channel for the release of ATP and inflammatory cytokines, as well as its activation in central glial cells, contributes to pain development. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 83 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…When PNI occurs, the distal nerve bers show Wallerian degeneration, and Schwann cells proliferate and aggregate to the endocardium. Multiple cytokines and growth factors interact with axons, participate in various stages of peripheral nerve injury repair and regeneration, and play an important role in the quality and speed of nerve regeneration [15,16] . Through pathological examination of sciatic nerve in rats, we also found that after sciatic nerve injury, the protective effect of myelin sheath was disrupted, axons showed vacuolar degeneration in different degrees, and in ammatory cells in ltrated obviously.…”
Section: Discussionmentioning
confidence: 99%
“…When PNI occurs, the distal nerve bers show Wallerian degeneration, and Schwann cells proliferate and aggregate to the endocardium. Multiple cytokines and growth factors interact with axons, participate in various stages of peripheral nerve injury repair and regeneration, and play an important role in the quality and speed of nerve regeneration [15,16] . Through pathological examination of sciatic nerve in rats, we also found that after sciatic nerve injury, the protective effect of myelin sheath was disrupted, axons showed vacuolar degeneration in different degrees, and in ammatory cells in ltrated obviously.…”
Section: Discussionmentioning
confidence: 99%
“…Panx 1, is an essential membrane channel for ATP and neurokine release, aside from its usual activation in central glial cells in pain generation and propagation (Penuela et al., 2013; Yang et al., 2019). Schwann cell Panx 1 plays a role in the synchronization of neuromediated inflammation and participates in neuropathic pain (Wang, Li, et al., 2022). Neuromediated inflammation correlates with pannexin 1 activation in Schwann cells, demonstrating that when Panx 1 channels are inhibited, it reduces neuropathic pain by arresting neuroinflammatory processes (Wang, Li, et al., 2022).…”
Section: Mechanisms Involved In the Pathophysiology Of Neuropathic Painmentioning
confidence: 99%
“…Schwann cell Panx 1 plays a role in the synchronization of neuromediated inflammation and participates in neuropathic pain (Wang, Li, et al., 2022). Neuromediated inflammation correlates with pannexin 1 activation in Schwann cells, demonstrating that when Panx 1 channels are inhibited, it reduces neuropathic pain by arresting neuroinflammatory processes (Wang, Li, et al., 2022).…”
Section: Mechanisms Involved In the Pathophysiology Of Neuropathic Painmentioning
confidence: 99%
See 2 more Smart Citations